(untitled) (Experimental biology, 2021)
Currently, one of the main sources of environmental pollution is oil and oil products. To solve the problems of soil cleaning, methods of biological reclamation have recently been successfully used, which are based on the activation of microbiological destruction of oil and oils products. The use of mixed strains of microorganisms allows the complete utilization of oil and oil products. The use of active hydrocarbon-oxidizing microorganisms in the cleaning of oil-contaminated objects is a promising and effective method. The aim of the work is to identify hydrocarbon-oxidizing microorganisms isolated from oil-contaminated soils of South Kazakhstan. From the oil-contaminated soils of South Kazakhstan, 5 active strains of hydrocarbon-oxidizing microorganisms have been isolated and identified, which can be promising for the disposal of oil-containing waste. Cultural-morphological and taxonomic features of microorganisms were revealed. Identification of the isolated cultures by molecular genetic characteristics were assigned to different physiological groups: Pseudomonas thivervalensis КМА4.1, Devosia neptuniae RMA7, Glutamicibacter arilaitensis MMA4, Aspergillus flavus Mach1, Penicillium chrysogenum Mach2. A phylogenetic analysis of the studied strains was carried out.